Clinical Experience with Pulse Dose Rate Brachytherapy for Conservative Treatment of Penile Carcinoma and Comparison with Historical Data of Low Dose Rate Brachytherapy. Issue 7 (July 2015) - Kamsu-Kom, L.; Bidault, F.; Mazeron, R.; Baratiny, C.; Martin, V.; Maroun, P.; Dumas, I.; Guemnie-Tafo, A.; Martinetti, F.; Gerbaulet, A.; Chargari, C.; Haie-Meder, C.
Abstract: Aims: To assess the efficacy of pulse dose rate (PDR) interstitial brachytherapy in the treatment of carcinoma of the penis and to compare with historical data of low dose rate (LDR) brachytherapy. Materials and methods: We reviewed the clinical records of 27 consecutive patients treated in our institution with exclusive PDR brachytherapy for a squamous cell carcinoma of the penis. The median tumour greatest diameter was 20 mm (range: 10–50 mm). Twenty-three patients (85%) had tumours limited to the glans and/or prepuce and four patients (15%) also had inguinal lymph node metastases. Implantations were carried out according to the Paris system and treatments were delivered with PDR brachytherapy. Results: The median brachytherapy dose was 60 Gy (range: 60–70 Gy). The median treated volume was 28 cm 3 (range: 8–62 cm 3 ). The median reference isodose rate was 0.4 Gy/pulse/h (range: 0.4–0.5 Gy/pulse/h). The median number of pulses was 150 (range: 120–175 pulses). With a median follow-up of 33 months (range: 6–64 months), tumour relapses in the penis were reported in four patients (15%). All patients with only local relapse ( n = 3) were successfully salvaged with partial amputation. The estimated overall survival rate at 3 years was 95% (95% confidence interval: 83–100%). No grade 3 or more acute reaction was observed. Delayed ulcerations and stenoses requiring at least one meatal dilatation were reported in two (9%) and five (22%) patients without local relapse. The treated volume was significantly correlated to the risk of clinically relevant delayed toxicity. Conclusions: The efficacy/toxicity results of PDR brachytherapy for the treatment of penile carcinoma are comparable with those obtained with LDR brachytherapy in historical cohorts. Highlights: We examined the efficacy/toxicity results of exclusive interstitial pulse dose rate brachytherapy for treatment of penile carcinoma. Local relapses were rare. All relapses within the penis were salvaged with surgery. The estimated overall survival rate at 3 years was 95% (95% confidence interval: 83–100%). Acute and delayed complications were comparable with historical data with low dose rate. The treated volume was correlated to the risk of delayed toxicity.